Students’ attitudes, beliefs and perceptions surrounding 2SLGBTQIA + health education and inclusiveness in Canadian physiotherapy programs - Codie A. Primeau; Holly T. Philpott; Kyle Vader; Janelle Unger; Christina Y. Le; Trevor B. Birmingham; Joy C. MacDermid (BMC Public Health, 2023)
Abstract Background Patients who identify as 2SLGBTQIA + report negative experiences with physiotherapy. The objectives were to evaluate student attitudes, beliefs and perceptions related to 2SLGBTQIA + health education and working with individuals who identify as 2SLGBTQIA + in entry-level physiotherapy programs in Canada and to evaluate physiotherapy program inclusiveness towards 2SLGBTQIA + persons. Methods We completed a nationwide, cross-sectional survey of physiotherapy students from Canadian institutions. We recruited students via email and social media from August-December 2021. Frequency results are presented with percentages. Logistic regression models (odds ratios [OR], 95%CI) were used to evaluate associations between demographics and training hours with feelings of preparedness and perceived program 2SLGBTQIA + inclusiveness. Results We obtained 150 survey responses (mean age = 25 years [range = 20 to 37]) from students where 35 (23%) self-identified as 2SLGBTQIA + . While most students (≥ 95%) showed positive attitudes towards working with 2SLGBTQIA + patients, only 20 students (13%) believed their physiotherapy program provided sufficient knowledge about 2SLGBTQIA + health and inclusiveness. Students believed more 2SLGBTQIA + training is needed (n = 137; 92%), believed training should be mandatory (n = 141; 94%) and were willing to engage in more training (n = 138; 92%). Around half believed their physiotherapy program (n = 80, 54%) and clinical placements (n = 75, 50%) were 2SLGBTQIA + -inclusive and their program instructors (n = 69, 46%) and clinical instructors (n = 47, 31%) used sex/gender-inclusive language. Discrimination towards 2SLGBTQIA + persons was witnessed 56 times by students and most (n = 136; 91%) reported at least one barrier to confronting these behaviours. Older students (OR = 0.89 [0.79 to 0.99]), individuals assigned female at birth (OR = 0.34 [0.15 to 0.77]), and students self-identifying as 2SLGBTQIA + (OR = 0.38 [0.15 to 0.94]) were less likely to believe their program was 2SLGBTQIA + inclusive. Older students (OR = 0.85 [0.76 to 0.94]) and 2SLGBTQIA + students (OR = 0.42 [0.23 to 0.76]) felt the same about their placements. Students who reported > 10 h of 2SLGBTQIA + training were more likely to believe their program was inclusive (OR = 3.18 [1.66 to 6.09]). Conclusions Entry-level physiotherapy students in Canada show positive attitudes towards working with 2SLGBTQIA + persons but believe exposure to 2SLGBTQIA + health and inclusiveness is insufficient in their physiotherapy programs. This suggests greater attention dedicated to 2SLGBTQIA + health would be valued.